Bioactive glass reinforced elastomer composites for skeletal regeneration: A review - Zeimaran, E.; Pourshahrestani, S.; Djordjevic, I.; Pingguan-Murphy, Belinda; Kadri, Nahrizul Adib; Towler, Mark Robert (Elsevier, 2015)
Biodegradable elastomers have clinical applicability due to their biocompatibility, tunable degradation and elasticity. The addition of bioactive glasses to these elastomers can impart mechanical properties sufficient for hard tissue replacement. Hence, a composite with a biodegradable polymer matrix and a bioglass filler can offer a method of augmenting existing tissue. This article reviews the applications of such composites for skeletal augmentation.